Kepercayaan Matematika dan Kemampuan Pemecahan Masalah Siswa SMP Negeri 13 Pekanbaru dalam Pelaksanaan Pembelajaran Pendekatan Realistic Mathematics Education (RME) - Yuanita, Putri (Jurnal Pilar Sains, 2011)
The purpose of this study was to determine the relationship of mathematics beliefs ofmathematics education students and their skills in problem solving. The sampleconsisted of 36 junior high school students with the subject Social Arithmetic andComparison. Data were collected by using Mathematics Beliefs Questionnaire andtest questions based on a topic distribution variabel random. The data were analyzeddescriptive statistics and inferensial statistics using Pearson correlation and t-test.The findings showed that there was a moderate correlation between the twovariables. There were no significant differences in terms of mathematical beliefs ofstudents but there is a significant difference to student’s skills in problem solvingconsepts and procedures based on student ability. The components of mathematicsbeliefs were divided into self beliefs in mathematics, belief in mathematics natureand beliefs in teaching and learning of mathematics. Most students especially thehigh level students had better beliefs in mathematics nature than in the other threecomponents. However the corelation of student’s beliefs with student’s skills inproblem solving was 0,675 and sig. 0.017. There was a significant relation betweenstudent’s beliefs and their skills in problem solving consepts and procedures.